Yang-May Ooi's The Flame Tree and the politics of environment in Malaysia - Zainal, Zainor Izat (Universiti Putra Malaysia Press, 2015)
The question of “Who has the power?” is often central in environmental politics, since power serves as a crucial mediation through which conflicts related to environmental problems are resolved (or not resolved). In this paper, the author analyses how power relations are unpacked in Yang-May Ooi’s The Flame Tree (1998) and what effects these relations have on land that is threatened by an environmentally-destructive project. Environmental politics within a society is usually carried out based on the political system that exists. In the case of Malaysia, it is within a semi-democracy that environmental politics takes place, which is characterised by liberal democracy (such as competitive elections, citizen participation and civil liberties) as well as authoritarian rule (dominant political ruling parties and strong interventionist states). This analysis compares and contrasts the novel with the Marxist theory of power, which is referred to in this paper as “power over” or the various ways that power is wielded in order to maintain the status quo. The author argues that although Ooi seems to subscribe to this traditional concept of power, representing the state, the capitalists and their ideologies as “having” power, she also undermines that “having” by constructing notions of “power to” – power that refers to an individual and/or a social group’s sense of worth, values, knowledge and potential to shape the course of actions and decisions related to the land – in order to create more equitable relations and structures of power. Ooi also presents this notion of “power to” as “problematic”: demonstrating how “power to” is often constricted by the forces of “power over”, as well as how the realisation of “power to” essentially hinges on paying more attention to ideological rather than coercive domination.